The Impact Of The Jukung Hias Tanglong Festival On The Social - Economic Aspects And Community Cohesion In Banjarmasin, South Kalimantan - Adista Anjar Diany (Maneggio, 2025)
Festivals are activities organized to celebrate important things in individuals or groups that are bound by custom, culture, tradition and religion in an area or environment. The Jukung Hias Tanglong Festival is organized by the South Kalimantan Provincial Government in celebration of the province's anniversary. The festival aims to showcase the beauty of the river and Banjar culture. The study seeks to contribute to presents the impact of Jukung Hias Tanglong on socio-economic and how festival in the region engenders to community cohesion. A quantitative survey utilizing convenience technique was used to gather data from a sample of 160 residents. The sampling for this study was all residents who lived and participated in the festival, aged 18 years and above. SmartPLS 4 was used to analyze the nature of the research hypotheses. The findings revealed festival to have a positive and significant effect on community cohesiveness, social and economic to local community. This research also recommends improving festival management professionally through the concept of sustainable tourism. Future research can examine sustainable tourism in Banjarmasin or other areas.